2014
DOI: 10.1016/j.jpowsour.2013.12.065
|View full text |Cite
|
Sign up to set email alerts
|

Lithium dynamics in carbon-rich polymer-derived SiCN ceramics probed by nuclear magnetic resonance

Abstract: We report 7 Li, 29 Si, and 13 C NMR studies of two different carbon-rich SiCN ceramics SiCN-1 and SiCN-3 derived from the preceramic polymers polyphenylvinylsilylcarbodiimide and polyphenylvinylsilazane, respectively. From the spectral analysis of the three nuclei at room temperature, we find that only the 13 C spectrum is strongly influenced by Li insertion/extraction, suggesting hand, the rotating frame relaxation rate T −1 1ρ results suggest that the slow motion of Li on the ms timescale may be affected by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Within the work of Reinold et al [12], the excellent performance of carbon-rich SiCN materials with outstanding stability and capacities up to 600 mAh g −1 has been demonstrated, including the discussion of the influence of the molecular polymer structure on the resulting ceramic microstructure and in consequence on the electrochemical performance of the material. By means of solid state NMR of lithiated and delithiated SiCN carbon phase was identified as a major lithium storage site [13], this finding being in agreement with the work of Fukui et al on SiOC materials [14]. Within our previous studies, we have also shown that composite anode materials comprised of SiCN/graphite [15] and SiCN/silicon [16] exhibit enhanced electrochemical properties compared to that of pure graphite and silicon, respectively.…”
Section: Introductionsupporting
confidence: 90%
“…Within the work of Reinold et al [12], the excellent performance of carbon-rich SiCN materials with outstanding stability and capacities up to 600 mAh g −1 has been demonstrated, including the discussion of the influence of the molecular polymer structure on the resulting ceramic microstructure and in consequence on the electrochemical performance of the material. By means of solid state NMR of lithiated and delithiated SiCN carbon phase was identified as a major lithium storage site [13], this finding being in agreement with the work of Fukui et al on SiOC materials [14]. Within our previous studies, we have also shown that composite anode materials comprised of SiCN/graphite [15] and SiCN/silicon [16] exhibit enhanced electrochemical properties compared to that of pure graphite and silicon, respectively.…”
Section: Introductionsupporting
confidence: 90%
“…After etching polymer-derived silicon-oxycarbide ceramics with hydrofluoric acid, silica domains are removed and the remaining structure is postulated to consist of a scaffolding of graphene networks with their surfaces decorated with mixed bonds of tetrahedral silicon bonded to both oxygen and carbon (Peña-Alonso et al, 2006). In Baek's study using SiCN as candidate for anode of Li-ion batteries to replace graphite anodes (Baek et al, 2014), the mixed bond tetrahedra of Si in SiCN is believed to act as an additional lithiation site. …”
Section: Resultsmentioning
confidence: 99%
“…Within recent years, anode materials based on carbon-rich SiOC and SiCN PDCs have been widely investigated for their lithium storage properties [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. It has been reported that carbon-rich silicon carbonitride (SiCN) recovers capacities as high as 600 mAh¨g´1 [25] while storing lithium mostly in the carbon phase [23,28]. The composite materials consisting of graphite/carbon-poor SiCN or precursor-derived Si(B)CN coated-multiwalled carbon nanotube (CNT) composite exceed by far the sum of the capacities of the single components [27,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…It signifies that more ordered carbon (higher La) might also enhance lithium storage performance. However, we assume that a decreased carbon content, which serves as the major active phase for reversible Li insertion in polymer-derived SiCN and SiOC ceramics [14,15,23,26], is the main reason for diminished electrochemical performance of BC 2 N.…”
mentioning
confidence: 99%